(untitled) (Journal of International Studies, 2023)
Organized crime syndicates are fuelling the dangerous and profitable world of drug trafficking making Southeast Asia suffered the consequences for centuries. The spread of opium by Chinese immigrants in the 1700s led to a devastating increase in drug addiction and trafficking. Uncontrolled opium smuggling was rampant, forcing the British government to act and ban the drug in 1952. Since Malaysia’s formation in 1963, the government has fought back with legal and enforcement measures, but drug trafficking from Thailand’s Golden Triangle has remained a serious threat to national security. This research paper investigates the drug trafficking situation in Malaysia and exposes the sinister threat that illicit drug entry poses to the country’s safety. Drawing upon primary data from interviews with enforcement officers, drug research experts, and academics, this qualitative study demonstrates that despite efforts to stop drug smuggling from the Golden Triangle, these criminal activities persist and endanger Malaysia’s political security.